Auperhydrophilic/Superhydrophobic: Tunable Wetting Patterns on Superhydrophilic/Superhydrophobic Hybrid Surfaces for Enhanced Dew‐Harvesting Efficacy (Adv. Mater. Interfaces 2/2020). Issue 2 (23rd January 2020) - Hou, Kongyang; Li, Xiaoyang; Li, Qiang; Chen, Xuemei
Abstract : This image depicts a superhydrophilic/superhydrophobic hybrid surface with superhydrophilic triangular patterns on the superhydrophobic substrate, fabricated using a laser ablation approach. The hybrid surface enables fast condensate droplet nucleation, directional transport, and efficient departure, exhibiting enhanced dew collection performance, compared to the uniform superhydrophilic or superhydrophobic surfaces. More details can be found in article number 1901683 by Xuemei Chen and co‐workers.